Factors Related to Reducing The Use of Plastic Bags in Kabupaten Bekasi - Ernyasih Ernyasih; Isnie Nurajizah Wijayanti; Triana Srisantyorini; Andriyani; Munaya Fauziah (Fakultas Kesehatan Masyarakat Universitas Muhammadiyah Jakarta, 2021)
The amount of waste in Indonesia in 2019 will reach 68 million tons and plastic waste is estimated to reach 9.52 million tons or 14 percent of the total existing waste. (Regional Representative Council of the Republic of Indonesia, 2017). In 2018 the total amount of waste in Bekasi Regency reached 152.3 tons per year. The composition of waste from plastic sources ranks first in the type of non-organic waste with a percentage of 9% (Bekasi Regency Environmental Service, 2018). Many impacts are caused by plastic bags on the environment, human health, and marine life. This study was conducted to determine the factors associated with reducing the use of plastic bags in the Bekasi Regency. The study design used was cross-sectional with primary data distributed through a questionnaire. A sample of 319 people, the retrieval is done by simple random sampling technique. Data analysis used chi square test (α = 0.05). Variables related to reducing the use of plastic bags are knowledge (p-value = 0.009 and OR = 0.465) and attitude (p-value = 0.038 and OR = 0.587). While the variables that were not related to the reduction in the use of plastic bags were age (p-value = 0.509), gender (p-value = 0.065), education (p-value = 0.667) and salary (p-value = 0.359). Factors that influence the reduction in the use of plastic bags in the Bekasi Regency are knowledge and attitudes. It is hoped that there will be an increase in the application of plastic bag costs in government policies regarding the plastic bag diet so that the use of plastic bags in the community can be minimized.